THE IMPACT OF MONETARY POLICY ON EMPLOYMENT ABSORPTION IN EAST NUSA TENGGARA USING THE ERROR CORRECTION MODEL (ECM) - Mau, Chiny Wilhelmina; Tiwu, Maria I Hewe; Tomasowa, Olivia L E` (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to estimate the effect of interest rates, inflation, and exchange rates on employment absorption in East Nusa Tenggara from 2000 to 2023 using the Error Correction Model (ECM) method. The results show that in the short term, interest rates and exchange rates do not have a significant effect on employment absorption. However, inflation has a significant impact on employment absorption in the short run. In the long term, all independent variables influence employment absorption. Therefore, to optimize employment absorption, especially in regions such as East Nusa Tenggara, there needs to be synergy between monetary, fiscal, and sectoral policies supported by structural reforms, appropriate inflation control, and the strengthening of labor-intensive industries and MSMEs.